Changes on the conformational and functional properties of soybean protein isolate induced by quercetin - Zhang, Yating; Hou, Ruiyang; Zhu, Beibei; Yin, Guangwei; Zhang, Jian; Zhao, Wenqi; Zhang, Junxi; Li, Taoran; Zhang, Zifan; Wang, Hongwu; Li, Zheng (Frontiers in Nutrition, 2022)
The conformational changes and functional properties of SPI induced by quercetin was investigated via fourier transform infrared (FTIR) spectroscopy, fluorescent spectroscopy, circular dichroism (CD) spectroscopy and molecular docking. A decrease in the fluorescence intensity and a blue shift in the maximum wavelength were observed due to the binding process with fluorescent residues. The analysis of Stern-Volmer equation showed that the fluorescence quenching induced by quercetin took the form of static quenching, and the binding stoichiometry between SPI and quercetin was 1:1. The values of △H and △S were both positive illustrating that hydrophobic interaction was the primary binding force between quercetin and SPI. Results of FTIR and CD indicated that the binding with quercetin changed the secondary structure of SPI, resulting in a partially unfolded and more flexible structure. SDS-PAGE confirmed there was no covalent interaction between the two constituents. Molecular docking demonstrated that there were stable configurations and high matching degrees in both 11S and 7S proteins with quercetin via hydrogen bonds and hydrophobic interactions. Meanwhile, modification by quercetin enhanced the foaming and emulsifying capacities of SPI. These findings might provide theory reference for elucidation the mechanism of polyphenols-proteins interaction and development of related food additive products in future.